(untitled) (Physical Education, Health and Social Sciences, 2025)
The Zikris represent a distinct community, primarily localized in the Makran region of Balochistan, Pakistan. Despite being an offshoot of the Hanafi school of thought, the Zikri community has historically remained at the periphery of academic discourse, often overlooked or misunderstood by both scholars and the broader public. Much of the tension surrounding their identity stems from the critiques of orthodox Muslim clergy, who primarily targets the Zikri departure from the traditional five-daily prayers (Salat), as the community places its central spiritual emphasis on the continuous, meditative remembrance of God (Zikir). Furthermore, the Zikris maintain a robust spiritual autonomy, operating under their own dedicated leadership and adhering to specific textual traditions that differ from Sunni clerical authority. The primary aim of this research is to bridge the gap in existing literature by exploring the internal religious beliefs and daily spiritual practices of the Zikri sect within the contemporary Pakistani context. The study finds that while the Zikris face significant external pressure regarding their Islamic identity, their faith is characterized by a resilient adherence to ancestral spiritual teachings and a unique liturgical structure. Ultimately, the purpose of this article is to document and validate the Zikri experience, advocating for a more nuanced understanding of sectarian diversity and providing a voice to a community that has long been rendered invisible by mainstream theological narratives.